Devise a mathematical model to represent the sediment at Al Anbar Thermal Power Station Outlet using GIS - Amin Al Hity, Ahmed (Iraqi Journal of Civil Engineering, 2013)
This research aims to study sediment discharges in Al Anbar Thermal Power Station in two phases the first phases include a follow-up study sediment load from the river by taking samples at different depths and different discharges, and noted measurements, calculations for each section while the second phases included an account of the tonnage of river sediment through the program depends on the equation of Meyer, to five sections (18, 26, 35.43, 45) with the observation results and do a comparison between the two phases. Research has included also employ technology of remote sensing and geographic information system GIS in the study of the waters of the Euphrates at thermal power plant after an analytical study was taken amount sediment and size in the study area and then link results with the geographic information system GIS for the purpose of producing layers represent the nature of the spatial distribution of these Sediments on the entire study area and the aerial imagery of software Google Earth with the use of the program (Arc view), one of the geographic information system software. The research concluded give recommendations for controlling the movement of sediment when the at Al Anbar Thermal Power Station Outlet through two main axes of them increase the flow velocity exceeds the critical velocity and the other includes the disposal of sediments away from the site of the station outlet.